The decision architecture of sustainable fashion: Evaluating green knowledge as a mediator in generation Z purchase intentions - Mustofa, Muhamad Jazuli; Maula , Defia Ifsantin (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Indonesia's textile and apparel industry, while being a major economic contributor due to fast fashion growth, faces criticism for its environmental impact, prompting brands like UNIQLO to adopt sustainable marketing practices. This study aimed to examine how green marketing tools specifically eco-labels, eco-brands, and environmental advertisements affect green purchase intention among Generation Z in Yogyakarta, with green knowledge assessed as a mediating factor. Method: Employing a quantitative method and purposive sampling of 250 respondents, the research applied Structural Equation Modeling (SEM) using SMART PLS 3.0 to analyze the data. Finding: The results demonstrated that eco-labels and environmental advertisements significantly enhance green purchase intention through the mediation of green knowledge, while eco-brands showed a positive but insignificant effect. The structural model achieved an R-square value of 0.620, confirming that the integrated variables explain 62% of the variance in green purchase intention, with environmental advertising identified as the most dominant predictor (F² = 0.388). Conclusion: The study concludes that strengthening eco-labeling and environmental advertising, alongside effective education, can significantly promote sustainable purchasing behavior among young consumers. However, the findings are limited to Generation Z in a single region, suggesting that future studies should incorporate broader demographics, geographic diversity, and additional influencing variables for wider applicability. Novelty/Originality of this article: This research contributes a localized structural model that evaluates the psychological mechanism of green knowledge as a mediator within the Indonesian fast-fashion industry.